The post-COVID-19 gender gap in the division of household labor - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2025)
This study provides a thorough examination of the evolving gender gap in time allocated to housework in the aftermath of the COVID-19 crisis. With data from the American Time Use Survey (2015-2022), our findings reveal a significant trend towards greater equality in the allocation of household tasks among couples, extending beyond the initial stages of COVID-19. Although the immediate response post-pandemic was not substantial, the subsequent period witnessed a sizable decrease of 16 minutes, representing 57% of the pre-pandemic gender gap related to housework time. Our research demonstrates an increase in men's domestic contributions, particularly in tasks related to interior cleaning. The pandemic's impact on housework time varied across personal characteristics, with younger individuals without a college degree and those without school-aged children making significant strides in closing the gender gap. Further results show that parents maintained a similar share of childcare responsibilities as before the pandemic, which may suggest that mothers mistrust fathers' ability to provide the same standard of care. This is also reflected by the fact that men have increased their participation in housework with their partner present. A supplementary analysis highlights the intensity of non-pharmaceutical interventions (NPIs) as a potential mechanism for changing gender roles. We show a more significant closure of the gender gap in household labor in areas with more intense NPIs. Our study presents suggestive evidence indicating that the ability to telework is also reducing the gender gap in domestic labor among couples.
Keywords: D13; J16; J22; 330; COVID-19; housework; gender; American Time Use Survey (ATUS)